p-Nitrophenyl carbonate promoted ring-opening reactions of DBU and DBN affording lactam carbamates - Vangala, Madhuri; Shinde, Ganesh P (Beilstein Journal of Organic Chemistry, 2016)
The amidine bases DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) and DBN (1,5-diazabicyclo[4.3.0]non-5-ene) display nucleophilic behaviour towards highly electrophilic p-nitrophenyl carbonate derivatives with ring opening of the bicyclic ring to form corresponding substituted ε-caprolactam and γ-lactam derived carbamates. This simple method presents a unified strategy to synthesize structurally diverse ε-caprolactam and γ-lactam compounds with a large substrate scope.
Keywords: carbonates; DBN; DBU; lactams; p-nitrophenyl